2019
DOI: 10.1002/ajp.23029
|View full text |Cite
|
Sign up to set email alerts
|

Meat eating in wild hamadryas baboons: Opportunistic trade‐offs between insects and vertebrates

Abstract: The consumption of meat may provide herbivorous animals with important nutrients that are scarce in their plant-based diet. Seasonal variation in plant food availability has been suggested to motivate dietary flexibility in a range of species and thus primates may seek more prey when key plant resources are unavailable.Alternatively, prey encounter rate may drive meat eating. Here we investigate patterns of meat eating in hamadryas baboons (Papio hamadryas) at Filoha, Awash National Park, Ethiopia. The Filoha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The resulting low level endotoxemia (circulating LPS) triggers immune responses to infection, including activating white blood cells (neutrophils and monocytes), increasing the expression of TLRs that detect bacterial cell wall molecules and heightening levels of circulating inflammatory proteins 152,153 . Though other nonape primate species opportunistically consume some meat, they do so at levels that many intersect with some ape species, but are much lower than most humans 154,155 . There is a small body of data that suggests that common chimpanzees, which eat varying amounts of meat but considerably less than many humans, are just as sensitive to LPS as humans are 99,142,156,157 .…”
Section: Unique Human Behaviors Have Likely Led To Increased Hexa‐acymentioning
confidence: 99%
“…The resulting low level endotoxemia (circulating LPS) triggers immune responses to infection, including activating white blood cells (neutrophils and monocytes), increasing the expression of TLRs that detect bacterial cell wall molecules and heightening levels of circulating inflammatory proteins 152,153 . Though other nonape primate species opportunistically consume some meat, they do so at levels that many intersect with some ape species, but are much lower than most humans 154,155 . There is a small body of data that suggests that common chimpanzees, which eat varying amounts of meat but considerably less than many humans, are just as sensitive to LPS as humans are 99,142,156,157 .…”
Section: Unique Human Behaviors Have Likely Led To Increased Hexa‐acymentioning
confidence: 99%
“…It is unclear from behavioral observations if baboons prefer certain body parts or organs to others, since prey taxonomy is usually the only information reported for baboon meat consumption. However, Rhine et al ( 1986 ) observed eggs being consumed by P. cynocephalus at Mukumi National Park, which may indicate a prominent dietary source of vitamin D. Finally, insects are sometimes included in baboon diets, as observed in locust and dragonfly consumption by P. cynocephalus and P. hamadryas troops (Rhine et al, 1986 ; Schreier et al, 2019 ). Locusts, along with a subset of other insect taxa, have an especially high vitamin D 3 content for body size (Oonincx et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meat eating is known in most of the baboon species at sites across Africa (Goffe & Fischer, 2016;Morris & Goodall, 1977;Rhine et al, 1986;Schreier et al, 2019). It is unclear from behavioral observations if baboons prefer certain body parts or organs to others, since prey taxonomy is usually the only information reported for baboon et al, 1986;Schreier et al, 2019). Locusts, along with a subset of other insect taxa, have an especially high vitamin D 3 content for body size (Oonincx et al, 2010).…”
Section: Skin Color and Dietary Influences On Mbd Developmentmentioning
confidence: 99%
“…Olive baboons (Papio anubis) prey upon at least 3 species of primates, 10 ungulates, 4 rodents, 3 hares, 1 bat, 4 herpetofauna and 6 species of bird (Strum 1975;Sommer et al 2016). Hamadryas baboons (P. hamadryas) can present a vertebrate predation rate of 2.8/100 hours of observation, preying on dik dik (Madoqua kirki), hares, Guinea fowl, among other preys (Schreier et al 2019). Yellow baboons (P. cynocephalus) hunt lizards, birds, and gazelles (Hausfater 1976; Rhine 1986).…”
Section: Introductionmentioning
confidence: 99%